Iron chelation studies using desferrioxamine and the potential oral chelator, 1, 2-dimethyl-3-hydroxypyrid-4-one, in normal and iron loaded rats. Issue 4 (April 1987) - Kontoghiorghes, G J; Sheppard, L; Hoffbrand, A V; Charalambous, J; Tikerpae, J; Pippard, M J
Abstract : A novel iron chelator, 1, 2-dimethyl-3-hydroxypyrid-4-one, and desferrioxamine were compared for their ability to remove iron and for their site of action in iron release in rats. Repeated intraperitoneal injections of the chelators in rats with widespread tissue labelling by 59Fe derived from transferrin showed comparable 59Fe mobilisation by each chelator in normal and iron loaded rats. Specific labelling of a chelatable "cold" iron pool in hepatocytes by 59Fe derived from ferritin showed this pool to be equally accessible to parenteral doses of both chelators and also to oral 1, 2-dimethyl-3-hydroxypyrid-4-one, which is an effective oral iron chelating agent that removes iron from parenchymal cells. This and other alpha-ketohydroxypyridines need further development as potential therapeutic agents in human iron overload.